2015
DOI: 10.1096/fasebj.29.1_supplement.1007.4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and adherence of intestinal mucus by commensal bacteria and the pathogen C. difficile

Abstract: Gut pathogens initially encounter the host at the gastrointestinal (GI) mucus layer making its regulation a crucial aspect of gut health. Few studies have addressed bacteria‐mucus adherence or mucus oligosaccharide utilization by commensal or pathogenic bacteria. To address this gap in knowledge, the interaction between mucus (human stool, HT‐29‐MTX cells and human ileal enteroids) and commensal bacteria (B. thetaiotaomicron, C. coccoides, C. butryicum, B. producta, A. muciniphila, F. prausnitzii, R. torques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…C. difficile has previously been shown to adhere to human mucus and to decrease mucin secretion in enteroids 47,48 . In addition, patients with CDI present decreased Muc2 levels and show alterations in mucin composition 48 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…C. difficile has previously been shown to adhere to human mucus and to decrease mucin secretion in enteroids 47,48 . In addition, patients with CDI present decreased Muc2 levels and show alterations in mucin composition 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens can also induce changes in secretion of mucin by goblet cells [74][75][76] , glycosylation of mucins 77 or reduction in mucus viscosity 78 . Several studies have shown that mucin facilitates C. difficile colonization 37,38,47,48,79 , probably because C. difficile binds to mucus from mice and humans 37,47,67,80,81 48 . They also showed a relationship between patients with recurrent CDI and a decrease of Muc2 and N-acetylgalactosamine (GalNAc) expression, along with an increase of N-acetylglucosamine (GlcNAc) and galactose residues 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation